The Critical Role of Test and Calibration in Modern Display Engineering - Muralidhar Manohar Shenoy, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive review explores the critical role of test and calibration processes in modern display manufacturing, examining their impact on quality control and production efficiency. The article investigates the evolution of display technologies, focusing on advances in pixel density, color reproduction, and refresh rates across LCD, OLED, and Micro LED platforms. It analyzes the implementation of automated optical inspection systems and advanced calibration methodologies, highlighting their contribution to defect reduction and manufacturing yield improvements. The article further demonstrates how standardized testing protocols and real-time monitoring systems have transformed production capabilities while ensuring consistent product quality. Additionally, the article examines the economic implications of these technological advancements and explores future trends in display manufacturing, particularly the integration of artificial intelligence and machine learning in quality control processes.
Keywords: Display Technology; Quality Control; Calibration Systems; Manufacturing Efficiency; Automated Inspection